About minimum variance hedging with futures - Zurita L., Salvador (Estudios de Administración, 2002)
Forward and Future contracts are frequently treated as synonymous, akin contracts playing the same economic function in hedging financial price risks. But they differ in fundamental ways. In the case of a forward contract, the counter-parties only interchange cash at the maturity of the contract; no money changes hands initially or during the lifetime of the contract. This difference implies different minimum variance hedge ratios when using a forward contract versus a futures contract for hedging purposes. In this paper we explore those for different types of underlying assets and different assumptions about the evolution of the risk-free interest rate.